Reseña de Douglas, E. S. y M. R. García-Doncel Hernández (2000), Practising English Consonants, Cádiz, Servicio de Publicaciones de la Universidad de Cádiz - David Levey (Pragmalingüística)
Se trata de reseña de Douglas, E. S. y M. R. García-Doncel Hernández (2000), Practising English Consonants, Cádiz, Servicio de Publicaciones de la Universidad de Cádiz.